Rancang Bangun Sistem Informasi Berbasis Website Lembaga Pelatihan Kewirausahaan (LPK) Ayostart dengan Metode Extreme Programming (XP) - Charine Dewi Rukminingtyas (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2022)
The Ayostart Entrepreneurship Training Institute is a training institution in Madiun City which was established with the aim of being a forum for every business actor to set up a business with optimal preparation so that it can increase the business to be more developed. The availability of trading land for UMKM actors from the Mayor of Madiun City, Mr. Maidi, made the agency conduct several business trainings to improve the economy of the people of Madiun City. All business processes that occur at LPK Ayostart are carried out offline at the Ayostart Office. This is deemed inefficient, so that the improvement of business processes that can be carried out to support the activities that occur at the Ayostart Entrepreneurship Training Institute (LPK) is to create a website-based entrepreneurship training information system so that the training can be accessed online and business actors who do not reside in Indonesia. Madiun can participate in activities that occur at the Ayostart Entrepreneurship Training Institute wherever they are. Making this website using the extreme programming method. Extreme Programming (XP) can be seen as a software development method that tries to increase the efficiency and flexibility of software development projects by combining simple ideas without compromising the quality of the software to be built. Keywords—: Entrepreneurship Training Institute, UMKM, Training, Website, Extreme Programming.